Localized Energy Poverty Index - Gonzalez, Angelica; Rivera, Leonardo; Manotas, Diego (International Journal of Energy Economics and Policy, 2024)
The impact of limited access to electricity varies based on the population. Our team evaluates the degree of deprivation experienced by different groups in order to identify energy poverty. Through the use of a multi-criteria methodology such as TOPSIS and Shannon entropy methods, we then establish an energy poverty index. This index allows us to compare populations and determine which are better or worse off. Our research produces a Localized Energy Poverty Index, which outlines the various factors that contribute to the energy poverty of a specific population. The localized index identifies poverty within a group while the Energy Poverty index combines this information to provide an energy-specific index. This index is useful in determining the feasibility of improving electricity service provision.